1970
DOI: 10.3329/jbcps.v28i2.5371
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma – An Unusual Presentation – A Case Report

Abstract: This case report is of a 50yrs old man who got admitted in BIRDEM Hospital in a state of unconsciousness for 5 hours .He is a known case of hypertension and diabetes mellitus for the last 12 years and was on insulin. Hypoglycemia was detected, treated with intravenous glucose and the patient regained consciousness. On further query he complained of repeated episodes of nausea, palpitation and sweating for the last 12 years. The episodes were initially labeled as hypoglycemia but blood sugar was never found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[55] Also, the conversion of vitamin A (retinol) to retinal [137] by the zincdependent alcohol dehydrogenase [138,139] may be clinically manipulated by zinc supplementation. [140] Worldwide, zinc deficiency in human subjects has since been reported to occur in physiological conditions where there is an increased requirement for zinc, for example, during childhood and pregnancy, [162] and it was originally observed that these deficiencies occurred in countries where primarily cereal proteins are consumed by the population. [1] Although, in both industrialized and developing countries, there may be inadequate dietary intake of zinc, inhibitors of zinc absorption are most likely the most common causative factor in zinc deficiency.…”
Section: Suboptimal Dietary Zinc Status and Deficiency: Clinical Manimentioning
confidence: 99%
“…[55] Also, the conversion of vitamin A (retinol) to retinal [137] by the zincdependent alcohol dehydrogenase [138,139] may be clinically manipulated by zinc supplementation. [140] Worldwide, zinc deficiency in human subjects has since been reported to occur in physiological conditions where there is an increased requirement for zinc, for example, during childhood and pregnancy, [162] and it was originally observed that these deficiencies occurred in countries where primarily cereal proteins are consumed by the population. [1] Although, in both industrialized and developing countries, there may be inadequate dietary intake of zinc, inhibitors of zinc absorption are most likely the most common causative factor in zinc deficiency.…”
Section: Suboptimal Dietary Zinc Status and Deficiency: Clinical Manimentioning
confidence: 99%
“…Catalytic, structural, and regulatory are the main biological roles played by the biometal [1]. In metalloproteins such as superoxide dismutase cytosolic CuZn, zinc plays a structural role while the copper functions as the catalytic site.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc deficiency is often characterized by compromised T-cell function, neurosensory injury and hindered healing processes. 26,27,28 However, in elevated concentrations, Zn is toxic. This divalent metal has been implicated in neurological disorders, in the disruption of iron homeo- stasis, and has also been shown to perturb cholesterol metabolism.…”
Section: Effect Of Concentration Of Zn +2 On Succinate Oxidationmentioning
confidence: 99%